Prevalence and molecular typing of rotavirus in children with acute diarrhoea in Northeastern Colombia. (2023)
After the introduction of the rotavirus vaccine, the number of rotavirus-associated deaths and the predicted annual rotavirus detection rate had slightly declined worldwide. Taking in account that in Colombia, Rotarix vaccine was introduced in 2009, the purpose of this study was to evaluate the presence of rotavirus A in children under five years who were treated for acute diarrhoea in Bucaramanga, Colombia and, moreover, to determine the genotypes of rotavirus present in those children. We performed an analytical cross-sectional study of rotavirus A in faecal samples from children up to five years of age. Stool samples were screened for rotavirus A using a lateral-flow immunochromatographic assay and confirmed using a VP6 sandwich ELISA. Genotyping of rotavirus A-positive samples was performed by PCR and sequencing of VP7 and VP4 genes. The overall prevalence of rotavirus was 30.53% (95% confidence interval [CI] 21.2 - 39.7). Most of the children with rotavirus (86.2%) had received two doses of the rotavirus vaccine. G3 strains accounted for the vast majority of cases (82.8%), followed by G12 strains (13.8%) and G3/G9 coinfections (3.4%). Among the P genotypes, P[8] was the most prevalent (69%), followed by P[9] (31%). The most common G[P] genotype combination was G3P[8], followed by G3P[9]. The main finding in this study was that rotavirus, in a Colombian region, is still an important pathogen in children under five years old, previously vaccinated. The results showed that different factors, such as kindergarten attendance, could explain the epidemiology and transmission of rotavirus in Bucaramanga.